PENGARUH CAPITAL INTENSITY RATIO,INVENTORY INTENSITY RATIO, OWNERSHIP STRUCTURE TERHADAP EFFECTIVE TAX RATE DENGAN KOMPENSASI RUGI FISKAL SEBAGAI VARIABEL MODERASI - Fadjriana, Icha (Balance : Jurnal Akuntansi dan Bisnis, 2019)
ABSTRACT: The purpose of this study is to determine whether the capital intensity ratio, inventory intensity ratio, ownership structure affect the Effective Tax Rate with compensation for fiscal losses as moderating. all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. This research is a quantitative study using multiple linear regression models. The results showed that inventory intensity ratio and institutional ownership had a significant effect on ETR, while Managerial Ownership did not affect ETR. The compensation for fiscal losses cannot moderate the relationship between inventory intensity ratio and Managerial Ownership to the effective tax rate. Whereas Institutional Ownership can be moderated by the effective tax rate.